The Arabidopsis a zinc finger domain protein ARS1 is essential for seed germination and ROS homeostasis in response to ABA and oxidative stress - Baek, Dongwon; Cha, Joon-Yung; Kang, Songhwa; Park, Bokyung; Lee, Hyo-Jung; Hong, Hyewon; Chun, Hyun Jin; Kim, Doh Hoon; Kim, Min Chul; Lee, Sang Yeol; Yun, Dae-Jin (Frontiers in Plant Science, 2015)
The phytohormone abscisic acid (ABA) induces accumulation of reactive oxygen species (ROS), which can disrupt seed dormancy and plant development. Here, we report the isolation and characterization of an Arabidopsis thaliana mutant called ars1 (aba and ros sensitive 1) that showed hypersensitivity to ABA during seed germination and to methyl viologen (MV) at the seedling stage. ARS1 encodes a nuclear protein with one zinc finger domain, two nuclear localization signal (NLS) domains, and one nuclear export signal (NES). The ars1 mutants showed reduced expression of a gene for superoxide dismutase (CSD3) and enhanced accumulation of ROS after ABA treatment. Transient expression of ARS1 in Arabidopsis protoplasts strongly suppressed ABA-mediated ROS production. Interestingly, nuclear-localized ARS1 translocated to the cytoplasm in response to treatment with ABA, H2O2, or MV. Taken together, these results suggest that ARS1 modulates seed germination and ROS homeostasis in response to ABA and oxidative stress in plants.